2011
DOI: 10.3386/w17657
|View full text |Cite
|
Sign up to set email alerts
|

The Best of Times, the Worst of Times: Understanding Pro-cyclical Mortality

Abstract: It is well known that mortality rates are pro-cyclical. In this paper, we attempt to understand why. We find little evidence that cyclical changes in individuals' own employment-related behavior drives the relationship; own-group employment rates are not systematically related to own-group mortality. Further, most additional deaths that occur when the economy is strong are among the elderly, particularly elderly women and those residing in nursing homes. We also demonstrate that staffing in nursing homes moves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
200
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(220 citation statements)
references
References 10 publications
14
200
6
Order By: Relevance
“…Notably, Miller, Page, Huff-Stevens, and Filipski (2009) show that this relationship holds for the very old and the very young suggesting that the mechanism for the result has to be something that is unrelated to job loss. More recent work by Huff-Stevens, Miller, Page, and Filipski (2011) suggests that these results are the consequences of increases in vehicular accidents and decreases in the quality of medical care for the elderly during boom times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Miller, Page, Huff-Stevens, and Filipski (2009) show that this relationship holds for the very old and the very young suggesting that the mechanism for the result has to be something that is unrelated to job loss. More recent work by Huff-Stevens, Miller, Page, and Filipski (2011) suggests that these results are the consequences of increases in vehicular accidents and decreases in the quality of medical care for the elderly during boom times.…”
Section: Discussionmentioning
confidence: 99%
“…However, as it turns out, studies based on aggregate data actually suggest the opposite, namely, that worsened macroeconomic conditions are associated with lower mortality e.g. Ruhm (2000), Filipski (2009), andFilipski (2011). At first glance, there does appear to be a tension between these two literatures.…”
Section: Uses the Panel Study Of Income Dynamicsmentioning
confidence: 99%
“…A concern which would invalidate this instrument as noted by Stevens et al (2015) is that local mortality rates are found to be associated with a community's cyclical fluctuations in economic activity resulting from cyclical variations in the local quality of care services. In China, this is less of a concern.…”
Section: Estimation Strategymentioning
confidence: 99%
“…There is a rich body of evidence on the potential pathways through which economic shocks could affect health outcomes Marmot 2002;Bezruchka, 2009;Miller et al, 2009;Stevens et al, 2011). There are theories to suggest that worsening economic conditions can have deleterious impacts on health outcomes but, equally, there are many hypotheses that predict the opposite.…”
mentioning
confidence: 99%
“…Stevens et al (2011) looked at the role of health care supply to help explain the aforementioned empirical conundrum whereby mortality rates decline when unemployment goes up. They investigated whether the fall in mortality rates in nursing homes can be explained by supply side factors.…”
mentioning
confidence: 99%